The effect of activator treatment on Class II malocclusion: Efektivitas perawatan dengan aktivator pada maloklusi Klas II - Nasyrah Hidayati; Fitria Mamile (Makassar Dental Journal PDGI Makassar, 2021)
Background: Malocclusion describes anomaly conditions in orthodontics, namely occlusion abnormal conditions. The preva-lence of malocclusion in Indonesia is still high around 80%. The management of malocclusion cases needs to pay attention ear-lier compared to being alert in adulthood. The treatment that can be performed is to use an activator functional appliance to pre-vent class II malocclusion. Objective: To review how the activator functional appliance was used in the treatment of Class II malocclusion. Methods: Scientific evidence is drawn from various literature to support this paper. Conclusion: Skeletal and dental changes can be achieved with the treatment of functional devices, activators. Activators can influence mandibular growth by increasing the rate of endochondral ossification in the condyles resulting in increased mandibular length in the treatment of Class II malocclusion. The success of the functional plane depends on the patient's developmental period, skeletal disorders, and patient cooperation.